Exploring Ethical, Cultural, and Transnational Competence Among International Healthcare Management Students: An Australian Perspective - Howard M; Tan KL; Jayasekara R (Journal of Healthcare Leadership)
Matylda Howard,1,2 Kuan Liung Tan,1 Rasika Jayasekara1 1Clinical & Health Sciences Academic Unit, University of South Australia, Adelaide, South Australia, Australia; 2Centre for Workplace Excellence, University of South Australia, Adelaide, South Australia, AustraliaCorrespondence: Matylda Howard, University of South Australia, Adelaide, South Australia, Australia, Tel +61 8 83021195, Email matylda.howard@unisa.edu.auIntroduction: Healthcare leaders face complex ethical challenges that can impact patient care and organizational integrity. For international healthcare management students pursuing leadership roles in Australia, these challenges are heightened by ethical, cultural, and transnational differences. This exploratory study examined the challenges faced by these students to establish foundational understanding of the competencies needed for effective ethical decision-making, cultural integration, and transnational readiness in diverse healthcare environments.Methods: Using a composite theoretical framework incorporating Cultural Relativism, Ethical Climate Theory, Institutional Theory, and Transnationalism, a 35-item instrument was adapted from three validated sources. A cross-sectional survey of 35 international postgraduate health services management students collected quantitative and qualitative data. Quantitative data were summarized using descriptive statistics, while thematic analysis, informed by the Gioia methodology, was applied to qualitative responses.Results: Key ethical challenges identified included healthcare inequity, resource allocation, and patient safety. Effective leadership practices emphasized fostering supportive work environments and promoting diversity. Participants demonstrated strong cultural competence, particularly in cultural awareness and cross-cultural communication, but highlighted the need for enhanced preparation in ethical decision-making and navigating transnational healthcare systems.Conclusion: The findings underscore the importance of transnational training programs that integrate cultural orientation, healthcare-specific language support, and ethical decision-making simulations. The Ethical, Cultural, and Transnational framework developed in this study provides a practical guide for embedding these competencies into leadership curricula, equipping international students to navigate the complexities of globalized healthcare systems effectively.Plain Language Summary: This study explored the challenges international healthcare management students face and emphasizes the importance of developing ethical, cultural, and transnational competencies to meet the expectations of Australia’s healthcare system. These students often encounter significant differences between their cultural values and the ethical standards of their host country. Building these skills is essential for ensuring they can provide ethical and culturally sensitive care while preparing for leadership roles in diverse healthcare environments. To understand these challenges, researchers surveyed 35 postgraduate healthcare management students from various cultural backgrounds. The survey explored their experiences with ethical issues in their home countries, their views on adapting to Australian healthcare standards, and their awareness of cultural diversity and preparedness to address ethical dilemmas. Participants also shared insights into effective leadership practices that promote ethical behavior. Key findings revealed that students identified major ethical challenges, including issues in healthcare access, resource allocation, and patient safety. While students showed strong abilities in cross-cultural communication and cultural awareness, they emphasized the need for more support in ethical decision-making. They highlighted the importance of leadership practices such as fostering inclusivity, transparency, and supportive work environments. This study suggests that international healthcare students need targeted support and training in cultural and ethical competence to prepare for leadership roles in countries like Australia. Education institutions can help students develop these skills to improve the quality of care for diverse populations and strengthen ethical practices in the global healthcare workforce.Keywords: cross-cultural comparison, culturally competent care, education, professional, ethical issues, organizational culture, professional competence